The Effect of Work Professionality and Organizational Commitment on the Performance of Discominfostandi Employees in Bekasi City in 2021 - Wahidin Septa Zahran; Iwan Irwansyah; Rousdy Safari Tamba; Parjaya (Asian Journal of Community Services, 2023)
The purpose of this study is to determine the how much influence of work professionality and organizational commitment on employee performance in Department of Communication, Information, Statistic and Code of Bekasi City. The Research method used is quantitative research in the form of survey. Samples this research are 97 employee. Methods of data collection using questionaires with likert scale. Conclusion this study : (1) Influence of work professionality on employee performance regression line = - 0, 661 + 0, 804 X1 hypothesis test with t-test result obtained by sig. = 0,000 and tcound =37, 564 > ttable = 1,661 H0 rejec (2) influence of organizational 1,684 + 0,840 X2 Hypothesis test with F-test result obtained by Sig. = 0,000 and Fcound =1045,360 > Ftable = 3,093 H0 reject. Conclusion of the research : (1) work professionality strong positive influence and significant on employee performance; (2) organizational commitment strong positive influence and significant on employee performance; (3) work professionality and organizational commitment together strong positive influence and significant on employee performance.